Comparative study of the photochemical stability of HDPE/Ag composites. (July 2018) - Grigoriadou, Ifigenia; Pavlidou, Eleni; Paraskevopoulos, Kostas M.; Terzopoulou, Zoi; Bikiaris, Dimitrios N.
Abstract: In the present study, HDPE composites containing different concentrations of silver (Ag) nanoparticles (0.5%, 1%, 2%, 3%, and 5 wt%) were prepared by melt mixing on a Haake-Buchler Reomixer. Composites in the form of thin films were exposed to UV irradiation at 280 nm at constant temperature (25 °C) and relative humidity (50%) for several hours. The samples were characterized for their photochemical stability with several methods. From FTIR spectroscopy it was found that new chemical compounds were formed during UV exposure containing carbonyl, vinyl, and hydroxyl/hydroxyperoxide groups. According to the spectra, the nanoparticles act as inhibitors to the photo-oxidation mechanism of the polymer matrix. Moreover, as the loading of nanoparticles increased, better protection was achieved. Further study of the samples was performed using tensile strength tests, showing that neat HDPE was affected significantly by UV irradiation, while its composites with Ag were affected in a lower extend. The greater the loading of the nanoparticles in the polymer matrix, the more they reduce the mobility of the molecules, thus inhibiting the chain scission of HDPE. Degree of crystallinity was also affected from UV exposure time and the addition of nanoparticles. Finally, the mechanism of thermal degradation of HDPE and its composite with 1 wt% Ag before and after UV exposure was studied by Pyrolysis-gas chromatography–mass spectroscopy (Py-GC/MS). Graphical abstract: Image 1 Highlights: Ag nanoparticles dispersed homogeneously in HDPE matrix. UV exposure degrades rapidly HDPE. Due to chemical scission new bonds (carbonyl, vinyl, and hydroxyl) are formed. Ag nanoparticles stabilize substantially HDPE against UV irradiation. Thermal decomposition mechanism of HDPE was not affected from Ag.